DEVELOPMENT OF THERAPEUTIC EXERCISES MANUAL FOR OROPHARYNGEAL DYSPHAGIA: PHASE I - Shabina Rana; Nayab Iftikhar (Journal Riphah College of Rehabilitation Sciences, 2024)
Objective: To reduce and eliminate aspiration and penetration ultimately, it was aimed to develop the indirect therapeutic exercises manual for patients with Oro-pharyngeal Dysphagia.